Analisis Yuridis Kepemilikan Hak Milik Oleh Warga Negara Asing Berdasarkan Wasiat (Studi Putusan Mahkamah Agung Nomor 1134/Pdt/2009) - Agnestisya Ningrum, Putri; Akib, Ma’ruf; Umar, Wahyudi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This study analyzes the Supreme Court Decision Number 1134/PDT/2009 which examines the validity of ownership of land titles where the recipient is known to be a foreign citizen based on a will. This issue is important because it concerns the principle of nationality in Indonesian agrarian law as well as the limitations of the legal subject of property rights holders. The purpose of the study is to examine the legal considerations of Supreme Court judges, the conformity of decisions with the Basic Agrarian Law, and its juridical implications on the practice of transfer of rights through wills. The research method used is normative legal research with a legislative approach, a conceptual approach, and a case approach. The results of the study show that the Supreme Court affirmed the prohibition of ownership of property rights by foreign citizens, even if obtained through a will, and emphasized the legal consequences in the form of nullity for the sake of law or the obligation to relinquish rights. This ruling strengthens the principle of nationality and provides legal certainty in the regulation of land ownership in Indonesia.